Improving internal logistics - A development case in manufacturing industry - Kukkonen, Harri (My University, 2019)
Developing company’s internal logistic processes and warehousing are of vital importance Not only for the profitability of a multi-factory conglomerate but as optimized logistic and warehousing solutions will bring cost savings for any manufacturer in the form of decreased stock-value and decreased need for safety stock. In addition, optimizing internal logistics will increase the utilization rate of logistics and warehouse workers, technology and machinery. The thesis investigates the internal logistics systems of a manufacturing unit located in Northern Ostrobothnia, Finland. The production facility utilizes several different kinds of manufacturing strategies within the production lines. The aim of this thesis is to create models for the picking of products and transporting them to the production line that would be suited for each production mode used at the site. As How, what and where items are stored in the factory’s warehouse plays an integral part of any internal logistics system, this too will be looked at critically in the thesis. XYZ and ABC analyses are utilized to optimize the warehouse. Furthermore, a tailor-made modification of the COI-index will be applied to the data. Together these three analyses form the basis for this study. In the course of the research, a validation of the use of the analysis tools selected will become evident and serve as a proof of concept for the analysis methodology and the tools created for the case company. The tools and methods created can be after initial pilot phase, be scaled for use at the entire global factory network of the case company.
Keywords: Internal Logistics; warehouse development; warehouse operations; Operational development; fi=Tuotantotalous|en=Industrial Management|; fi=Master's Degree Programme in Industrial Management|